AL GHAZALI'S RESPONSIBILITY AND IBNU RUSYD'S DEFENSE AGAINST THREE QUESTIONS OF METAPHYSICS OF PHILOSOPHERS - Surajiyo Surajiyo (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
There is a controversy between Al Ghazali and Ibn Rushd in responding to three metaphysical issues, namely the Qadim of nature, God does not know about small matters or events, Denial of bodily resurrection. On the one hand, Al Ghazali considers that the philosophers who think and believe in these three metaphysical issues are considered infidels. On the other hand, Ibn Rushd thinks that the infidel laws that have been imposed by Al Ghazali against the philosophers are not justified. This research method uses a description method, namely a literary discussion, especially literature that discusses the thoughts of Al Ghazali and Ubnu Rushd. In this method, classification, data processing and conclusions are carried out. Thus, comparative methods, analytical methods, and synthesis methods are needed. Terdapat kontroversial antara Al Ghazali dan Ibnu Rusyd dalam menanggapi tiga persoalan metafisika yakni Qadimnya alam, Tuhan tidak mengetahui tentang soal-soal atau peristiwa-peristiwa kecil, Pengingkaran terhadap kebangkitan jasmani. Disatu pihak Al Ghazali menganggap bahwa para filosof yang berpendapat dan yang memepercayainya ketiga persoalan metafisika itu dianggap kafir. Dilain pihak Ibnu Rusyd beranggapan bahwa hukum kafir yang telah dijatuhkan oleh Al Ghazali terhadap para filosof itu tidak dibenarkan. Metode penelitian ini dengan metode deskripsi yaitu pembahasan yang bersifat literer khususnya literartur yang membahas pikiran Al Ghazali dan Ubnu Rusyd. Di dalam metode ini dilakukan klasifikasi, pengolahan data dan peyimpulan. Dengan demikian diperlukan metode komparatif, metode analisa, dan metode sintesa.